2000
DOI: 10.1046/j.1440-1827.2000.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal carcinogenesis induced by ferric nitrilotriacetate in mice, and protection from it by Brazilian propolis and Artepillin C

Abstract: The protective effect of Brazilian propolis and its extract Artepillin C against ferric nitrilotriacetate (Fe-NTA)-induced renal lipid peroxidation and carcinogenesis was studied in male ddY mice. Fe-NTA-induced renal lipid peroxidation leads to a high incidence of renal cell carcinoma (RCC) in mice. Administration of propolis by gastric intubation 2 h before or Artepillin C at either the same time, 2 h, or 5 h before the intraperitoneal injection of Fe-NTA (7 mg Fe/kg) effectively inhibited renal lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
25
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 18 publications
7
25
0
3
Order By: Relevance
“…There are no available in vivo studies investigating the effects of CAPE on MM cells. However, results supporting our study have been reported in various studies investigating the in vivo effects of CAPE on various cancer models (42,43). Among them is the in vivo study by Onori et al in which, after intraperitoneal CAPE at 10 mg/kg was administered to BALB/c mice, tumor growth was found to be reduced within 77 days, the latent period of the tumor was increased 2-fold, and no differences were observed in the fibrosis or inflammation in either the carrier-or CAPE-treated animals with no other tissue/organ damage.…”
Section: Discussionsupporting
confidence: 92%
“…There are no available in vivo studies investigating the effects of CAPE on MM cells. However, results supporting our study have been reported in various studies investigating the in vivo effects of CAPE on various cancer models (42,43). Among them is the in vivo study by Onori et al in which, after intraperitoneal CAPE at 10 mg/kg was administered to BALB/c mice, tumor growth was found to be reduced within 77 days, the latent period of the tumor was increased 2-fold, and no differences were observed in the fibrosis or inflammation in either the carrier-or CAPE-treated animals with no other tissue/organ damage.…”
Section: Discussionsupporting
confidence: 92%
“…One finding indicated that DHCA exhibited inhibitory effects on renal carcinogenesis as a result of its oxy-radical scavenging property (Kimoto et al, 2000). Matsuno et al (1997) reported that DHCA was one of the effective anti-tumor compounds found in propolis and Kimoto et al (2001) and Kimoto et al (1998) showed that the DHCA is capable of reducing the mass of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been characterized variously as an anti-bacterial, 6,7) anti-viral, 8) anti-inflammatory, 9-11) anti-oxidant, 12) and anti-carcinogenesis agent. 13,14) Obesity is caused by various environmental and genetic factors.15) One of the main environmental factors causing obesity is the intake of a high-fat diet, now common in many populations. A diet-induced obesity animal model has been developed to investigate human obesity, replicating the effects of human obesity more accurately than genetic obesity models.…”
mentioning
confidence: 99%